Advanced photogrammetric techniques for heritage conservation: a case study of the visual and architectural preservation of the Jagannath Temple, Puri - Chatterjee, Amit; Mohapatra, Bharati (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
The Jagannath Temple in Puri, India, positions as a testimony to a rich cultural, religious and architectural heritage. However, rapidly changing fabric of cities and urbanization poses substantial threat to its heritage significance and aesthetic integrity. This study proposes a comprehensive qualitative and photogrammetric approach to assess and document the visual integrity of the heritage value of Jagannath Temple precinct. It employs high-resolution aerial and terrestrial photogrammetry. The project contributes in generating a detailed 3D model and orthophotos of the heritage precinct. These digital depictions will enable precise analysis of architectural elements and spatial relationships. This study contributes as a vital tool for conservation planning and informed decision-making by safeguarding the sustainable preservation of this iconic cultural asset.